Curing and infiltration behavior of uv-curing thermosets for the use in a combined laser sintering process of polymers - Wudy, Katrin (Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
The investigation in this study addresses a new additive manufacturing process, which enables the production of multi-material parts consisting of thermosets and thermoplastics. A liquid thermoset resin will be applied with a micro value syringe in the laser sintering (LS) system. The liquid thermoset reacts parallel to the laser exposure of the thermoplastic powder. Therefore, in this study the UV curing and the infiltration behavior of the thermoset will be investigated under process relevant conditions. The investigations show a strong temperature dependent absorption of the liquid in the powder bed, whereas, the surface tension of the liquid plays a minor role. Furthermore, the UV curing of the thermosets takes place at low interaction times and at lamp powers between 100 and 300 mW/cm2.,.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Laser sintering; Multi-material part; Thermoplastic; Thermoset